Al-Nihayah fi Al-Fitan wa Al-Malahim - Maula Sari; syafiul Huda (Al-Bukhari : Jurnal Ilmu Hadis, 2020)
The Day of Judgment is a an undeniable situation which muslims believe as part of the basic pillar of Iman.. A book that focuses on collecting news about the Day of Judgment, namely al-Nihāyah fī al-Fitan wa al-Malāḥim. This paper examines the book by Imam Ibn Kaṡȋr using descriptive-analytical methods and a book analysis study approach (bahtsul polar). Formulation of the problem; to explore the writing methods, the characteritics of the book, the advantages and the disadvantages. This article finds that; first, the method of writing the Nihāyah book is not systematic, the discussion is mixed with each other even though it is not that large, and there are no special signs that distinguish the topic of discussion. Second, the characteristics of the book al-Nihāyah fī al-Fitan are classified as hadith books whose main characteristics include the matan and its sanad. Third, the use of the hadith book mu'tabar as the main reference and the lack of unsystematic placement of titles and subtitles. However, the drawbacks were not that many compared to the advantages.